Fabrication Strategies and Optoelectronic Applications of Perovskite Heterostructures. Issue 5 (28th December 2021) - Cheng, Xiaohua; Han, Ying; Cui, Bin‐Bin
Abstract: Metal halide perovskites (MHPs) are emerging low‐cost and multifunctional semiconductor materials. They have been widely used in optoelectronic devices such as perovskite solar cells, light‐emitting diodes, photodetectors, memristors, and lasers. Developing new MHPs, defects passivation, optimizing device structures, and packaging techniques are all effective methods to improve photoelectric performance and stability of perovskite devices. Particularly, the fabrication of perovskite/perovskite heterostructures (PPHSs) is a novel and arresting method to obtain stable and high‐performing optoelectronic perovskite devices since it can passivate defects, regulate energy gaps, and provide new carrier transmission modes of MHPs for multiple semiconductor applications. In this paper, representative fabrication strategies of PPHSs including films and single‐crystal heterostructures are reviewed, and their applications in optoelectronic devices are summarized. Furthermore, the challenges and prospects of PPHSs are discussed based on the current status. Abstract : Fabrication strategies of perovskite/perovskite heterostructures (PPHSs) are summarized from different dimensions and morphologies. Applications of PPHSs in solar cells, light‐emitting diodes, photodetectors, and lasers are presented. The challenges encountered in the synthesis and applications of PPHSs are proposed, and the prospects of optoelectronics based on PPHSs are looked at.